-6(n+2)+15=-2n-15

Simple and best practice solution for -6(n+2)+15=-2n-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(n+2)+15=-2n-15 equation:


Simplifying
-6(n + 2) + 15 = -2n + -15

Reorder the terms:
-6(2 + n) + 15 = -2n + -15
(2 * -6 + n * -6) + 15 = -2n + -15
(-12 + -6n) + 15 = -2n + -15

Reorder the terms:
-12 + 15 + -6n = -2n + -15

Combine like terms: -12 + 15 = 3
3 + -6n = -2n + -15

Reorder the terms:
3 + -6n = -15 + -2n

Solving
3 + -6n = -15 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
3 + -6n + 2n = -15 + -2n + 2n

Combine like terms: -6n + 2n = -4n
3 + -4n = -15 + -2n + 2n

Combine like terms: -2n + 2n = 0
3 + -4n = -15 + 0
3 + -4n = -15

Add '-3' to each side of the equation.
3 + -3 + -4n = -15 + -3

Combine like terms: 3 + -3 = 0
0 + -4n = -15 + -3
-4n = -15 + -3

Combine like terms: -15 + -3 = -18
-4n = -18

Divide each side by '-4'.
n = 4.5

Simplifying
n = 4.5

See similar equations:

| n*2-4/3= | | 2x+8=-13-3x | | SH*x=915 | | 24=2(-8-L) | | 15822.65/n=19795.81 | | (5u-8)and(3u-4)u=9 | | 2c-7=54 | | -7x^2+11x-4=0 | | 24-4x=-2x+6 | | 3/10*3 | | -4=4(x-5) | | (6)(-9)= | | -7x^2+7x+12=0 | | -6y-2y-1=0 | | 19795.81=15822.65/n | | 7x+2=28+5c | | y=0.9x+7.7 | | 2*3/12 | | 1.5(X+2)=11 | | 11x^2+6x-9=0 | | w=3w-6 | | (4x+3)-(2x+9)= | | 3n-3=25 | | f(x)=12x^2+18xe | | 9+6lnx=17 | | 3(m-5)=2(5m-11) | | 8m+20=16m-4 | | 5x-48=82 | | 3y+178=253 | | (5x+8)-(-6x+9)= | | 4x-27=73 | | 1080*x=967 |

Equations solver categories